The Difference between the Management of Human Resources and Personnel Management - Elzlatni, Naser; Elkikhia, Faisal (Dirasat in Economics and Business, 2011)
According to the article human resource management,2013 human resource management is the process of managing people in organizations in a structured and thorough same article gives a second definition, which is macrooriented unlike the first one. This second definition states that human resources management people in organizations from a roach of defining Human resources management from a macro perspective, it makes it more encompassing to the different dynamics of managing people rather than from the narrow oriented perspective that distinguishes human resources management from a microoriented perspective of personnel management (human resources management,2013, personnel management,2013) Human resources management can be defined as the effective use of human resources in an organization through the management of people related activities. In this case, it becomes the core in the deliberate administration of people-related activities (human resources management,2013).